Cultural Imperialism of the Korean Wave and its Impact on Thai Society - Kamon, Butsaban (Journal of Ecohumanism, 2024)
As the Korean Wave in Thailand continues to gain sensational popularity, along with the development of the Korean Wave, the negative influence of the Korean Wave in Thailand has also been highlighted. The beauty of Korean-style whitening provides a new symbol of beauty in Thailand, and the desire to unconsciously imitate Korean beauty can be said to have political implications that go beyond simply personal desires and superficial issues. This research analyzes how the whitewashing of K-pop as a cultural imperialist element of the Korean Wave is affecting Thai society. Specifically, in-depth interviews were conducted with Thai Korean Wave fans who envy K-pop idols. Based on the interview results, it analyzed Thai beauty standards and perceptions of whitewashing that have become typical through K-pop and the political meaning of the stereotypical beauty standard of “white skin” and its influence on Thai society.